Weekly kilovoltage cone-beam computed tomography for detection of dose discrepancies during (chemo)radiotherapy for head and neck cancer. (21st October 2015) - Hermans, Bregtje C.M; Persoon, Lucas C.G.G; Podesta, Mark; Hoebers, Frank J.P; Verhaegen, Frank; Troost, Esther G.C
ABSTRACT: Background . Use of highly conformal radiotherapy in patients with head and neck carcinoma may lead to under-/overdosage of gross target volume (GTV) and organs at risk (OAR) due to changes in patients' anatomy. A method to achieve more effective radiation treatment combined with less toxicity is dose-guided radiotherapy (DGRT). The aim of this study was to evaluate discrepancies between planned and actually delivered radiation dose in head and neck patients and to identify predictive factors. Methods. In this retrospective analysis, 20 patients with cT2-4 N0-3 M0 carcinoma originating from oropharynx, oral cavity, larynx and hypopharynx (Cohort 1), and seven patients with cT1-4 N0-3 M0 nasopharyngeal carcinoma (Cohort 2) treated with primary (chemo)radiotherapy and undergoing weekly kV-CBCT scans were included. Radiation dose was recalculated on 184 kV-CBCT images, which was quantified by D95% (GTV), Dmean (parotid and submandibular glands) and D2% (spinal cord). Predictive factors investigated for changes in these dose metrics were: gender, age, cT/N-stage, tumor grade, HPV-status, systemic therapy, body mass index at start of treatment, weight loss and volume change over the duration of the radiotherapy. Results. There was no significant difference between the planned and delivered dose for GTV and OARs of Week 1 to subsequent weeks for Cohort 1. In Cohort 2, actually delivered Dmean to parotid glands was significant higher than planned dose (1.1 Gy, p = 0.002). No clinically relevant correlations between dose changes and predictive factors were found. Conclusion. Weekly dose calculations do not seem to improve dose delivery for patients with tumors of the oral cavity, oropharynx, larynx and hypopharynx. In patients with nasopharyngeal carcinoma, however, mid-treatment imaging may facilitate DGRT.